2000
DOI: 10.3354/meps204013
|View full text |Cite
|
Sign up to set email alerts
|

Production and consumption of dimethylsulfide (DMS) in North Atlantic waters

Abstract: Production and consumption of dimethylsulfide (DMS) were studied in surface waters of the northwest Atlantic between latitude 32°and 45°N during May 1998. The kinetics of DMS production by the whole planktonic community were studied in short-term (3 h) experiments using additions of dissolved dimethylsulfoniopropionate (DMSP d ) (0 to 3000 nM). Measurements of DMS production and DMSP d consumption showed that the DMS production rate increased in direct proportion to the concentration of added DMSP d . This rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 59 publications
2
34
1
Order By: Relevance
“…Samples of both DMSP d and DMSP T were preserved by adding 50 µL of a 50 % sulfuric acid (H 2 SO 4 ) solution to the 5 mL tubes, which were then stored at 4 • C in the dark until analysis in the laboratory. DMSP concentrations were determined as DMS through hydrolysis with a 5 N solution of NaOH, purging and cryo-trapping in liquid nitrogen, followed by analysis on a Varian 3800 Gas Chromatograph equipped with a pulsed flame photometric detector (PFPD, Varian 3800) with a detection limit of 0.1 nmol L −1 (Scarratt et al, 2000;Lizotte et al, 2012;Galindo et al, 2016). All DMSP samples were calibrated against multiple micro-injections of a 100 nmol L −1 solution of standardised dimethyl-B-propiothetin (DMPT from Research Plus) hydrolysed with a 5 N solution of NaOH.…”
Section: Dmsp and Dms Concentrationsmentioning
confidence: 99%
“…Samples of both DMSP d and DMSP T were preserved by adding 50 µL of a 50 % sulfuric acid (H 2 SO 4 ) solution to the 5 mL tubes, which were then stored at 4 • C in the dark until analysis in the laboratory. DMSP concentrations were determined as DMS through hydrolysis with a 5 N solution of NaOH, purging and cryo-trapping in liquid nitrogen, followed by analysis on a Varian 3800 Gas Chromatograph equipped with a pulsed flame photometric detector (PFPD, Varian 3800) with a detection limit of 0.1 nmol L −1 (Scarratt et al, 2000;Lizotte et al, 2012;Galindo et al, 2016). All DMSP samples were calibrated against multiple micro-injections of a 100 nmol L −1 solution of standardised dimethyl-B-propiothetin (DMPT from Research Plus) hydrolysed with a 5 N solution of NaOH.…”
Section: Dmsp and Dms Concentrationsmentioning
confidence: 99%
“…Kiene and Service (1991) found that rates of DMS biological production and consumption increased when temperatures were between 16 and 30°C, and that, because of low biological activity, biological production rates were low at 4 and 49°C. Scarratt et al (2000) showed that production rates of DMS were higher when water temperatures were between 16 and 20°C. However, in this study, water temperature and DMS production or consumption rates were not correlated.…”
Section: Vertical Profiles Of Dms and Dmspmentioning
confidence: 99%
“…and G. flagellare, may dominate the production and distribution of DMS and DMSP in this region of the NW Atlantic at this time of year. The data presented here comprise part of a larger data set covering several years of observations in this region, including in situ and shipboard incubations, which is described in part elsewhere (Scarratt et al 2000b). …”
Section: Introductionmentioning
confidence: 99%